(untitled) - Locker, Kitty O. (Texas, 2017)
A unique approach to a hands-on course, written by the same author of Business and Administrative Communication, this completely new approach is devised and created with the assistance of a community college colleague. The innovative module structure allows instructors to focus on specific skills and provides greater flexibility for short courses and different teaching approaches. While grounded in solid business communication fundamentals, this paperback takes a strong workplace activity orientation which helps students connect what they learn to what they do or will do on the job.
Keywords: Giao tiếp trong kinh doanh,Business communication